ChemInform Abstract: Microwave‐Assisted Silica‐Promoted Solvent‐Free Synthesis of Triazoloquinazolinone and Benzimidazoquinazolinones. Issue 52 (24th December 2013) - Krishnamurthy, G.; Jagannath, K. V.
Abstract A simple and environmentally benign silica‐promoted multicomponent reaction for the synthesis of triazolo‐ or benzimidazoquinazolinone heterocycles is developed.